2007
DOI: 10.1111/j.1369-7625.2007.00463.x
|View full text |Cite
|
Sign up to set email alerts
|

The UCLan community engagement and service user support (Comensus) project: valuing authenticity, making space for emergence

Abstract: Objective To develop and evaluate service user, carer and community involvement in health and social care education.Background Despite the high policy profile of involvement issues, there appear to be no published accounts of schemes that have used a systematic whole-faculty approach to community engagement in health and social care higher education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Access to funding and issues related to payment, are reported as a perennial problem (Downe, 2007;Minogue, 2009). Gaining access to users from seldom heard vulnerable groups, who often have the greatest need, is highlighted as a challenge (Agnew & Duffy, 2010;Furness et al, 2010).…”
Section: Uses Of the Conceptmentioning
confidence: 99%
See 2 more Smart Citations
“…Access to funding and issues related to payment, are reported as a perennial problem (Downe, 2007;Minogue, 2009). Gaining access to users from seldom heard vulnerable groups, who often have the greatest need, is highlighted as a challenge (Agnew & Duffy, 2010;Furness et al, 2010).…”
Section: Uses Of the Conceptmentioning
confidence: 99%
“…Users and academics work together to make decisions (Downe et al, 2007;Minogue et al, 2009;Morgan & Jones 2009). …”
Section: Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…This requires the investment of time and resources. Pioneers in this field (Downe et al, 2007) have identified the need for authenticity in order for engagement to be successful. The recognition and understanding that effective service user engagement requires careful planning with support networks for service users and academics.…”
Section: Findings Findings -The Academic Perspectivementioning
confidence: 99%
“…364,365 We drew pragmatically on a range of techniques that have previously been used in community engagement for addressing health issues. The University of Central Lancashire (UCLAN) model, 366 built on participatory action research, is perhaps the best known in the UK. Although having a number of techniques and principles in common, developing a model for community engagement in a complex intervention context involved a different resolution of the principles underpinning participatory action research.…”
Section: Aims and Approachesmentioning
confidence: 99%